2017
DOI: 10.1111/nicc.12305
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the needs of critical care patients after discharge home: a qualitative exploratory study of patient perspectives

Abstract: Whilst there are commonalities in the problems faced by critical care survivors, recovery is highly individualized, and current support services do not have sufficient flexibility to cater for this. This study shows that many survivors experience after-effects of critical care that outlast the support they are given. These longer-term survivors are often excluded from research studies because of fears of recall bias, resulting in poor understanding of their experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Lack of communication between services often resulted in a lack of understanding of the impact critical illness can have on patients and families. Allum et al, 2018, p 318), pointed out that;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of communication between services often resulted in a lack of understanding of the impact critical illness can have on patients and families. Allum et al, 2018, p 318), pointed out that;…”
Section: Resultsmentioning
confidence: 99%
“…Given the overall small number of ICU survivors that individual GPs or other community healthcare professionals see, this is perhaps not surprising, but does highlight a need for education on ICU survival and its longer‐term impact on patients and families. The need to address ICU survivors’ health and psychosocial needs post‐ICU has been recognised for some time by ICU healthcare professionals and some policy makers (NICE, 2009); nevertheless, we still need to develop models of care that incorporate follow‐up care and ongoing support throughout the recovery and subsequent survivorship trajectory and that are person‐centred (Allum et al, 2018; Prinjha et al, 2009; Tembo et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Two recent qualitative studies explored patients’ and relatives’ perspectives about hospital discharge after an ICU admission. Both emphasised the benefits of tailored patient-centred information flow to help navigate this process [6,36].…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation is that recall bias may have occurred, as the period of time between the interviews and completion of the VR program was on average twelve months (patients) and six months (professionals and managers). However, another qualitative research study of the support needs of survivors of critical care found no difference in the stories of patients who underwent critical care up to five years previously [41]. This would suggest that our findings are reliable.…”
Section: Strengths and Limitationsmentioning
confidence: 53%